The Grand Condé in exile - Inglis-Jones, J; Inglis-Jones, James John (1995)
﻿ This thesis looks at the career of the Grand Condé - Louis II de Bourbon, Prince de Condé - between 1652 and 1660. During this period the prince was in exile in the Spanish Netherlands. As a consequence of his power and status in France the prince's exile had a decisive impact not just upon the politics of the captaingeneral's court in Brussels, but more widely, upon the foreign policy of Cromwell's Protectorate, Philip IV's government in Madrid, the regime of Cardinal Mazarin in Paris and the Franco-Spanish war. International relations between France and Spain during the 1650's have been largely ignored by historians, so too has French political history in this period. Yet, the 1650's were a vital decade for France and Spain both historically and historiographically. The period saw the final stage of the costly and attritional conflict between the two 'great' crowns, whilst in France the regime of Cardinal Mazarin was the last ten years of government by a cardinal-minister before Louis XIV's declaration of personal rule in 1661. This has assumed enormous significance for historians many of whom see it as an important period of transition. Ten major European archives have been consulted to build a detailed picture of the impact of Condé's exile upon politics within France and the war being fought in the Flanders theatre. The cardinal's regime existed throughout the 1650's in an environment of acute uncertainty and instability whilst it was by no means clear that the war with Spain was a demonstration of an 'ascendant' France dealing the death blows to a 'declining' Spain. By raising questions about France's 'rise' to European supremacy and the internal stability of Mazarin's regime the thesis rejects the straightforward terms in which this period has been treated. In particular, using the example of Condé and placing his exile and Mazarin's regime in the context of aristocratic politics, it demonstrates that there were no indications that grandee power was in decline. Indeed, the thesis argues that the power of the grands as a crucial element in the power structure of Ancien Regime France, was set to continue into the next century.